Ultrasensitive Nano-ELISA for Detecting Sulfadimethoxine in Chicken Tissue. (29th December 2013) - Peng, Chi-Fang; Duan, Xiao-Hui; Pan, Qiu-Li; Liu, Li-Qiang; Xue, Feng
Abstract : It is challenging to obtain a highly sensitive enzyme-linked sorbent immunoassay (ELISA) method for the rapid screening of veterinary drug residue in animal tissues. Here we present that a simple and sensitive detection for sulfadimethoxine (SDM) residue in animal tissues was achieved by utilizing a bioconjugate of gold nanoparticles and enzyme-labeled antibody as signal probe in enzyme-linked sorbent immunoassay (ELISA). The developed nano-ELISA has increased the sensitivity of a traditional ELISA for SDM by 20-fold. The sensitivity of this ELISA was 5 pg/mL in buffer, and the detection limit (LOD) of 0.2 µg/kg can be obtained after chicken liver was simply extracted by buffer. This simple and sensitive method can be used to improve the sensitivity of ELISA methods for various small molecule contaminants.